1998
DOI: 10.1182/blood.v92.3.946
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate–Induced Shedding of CD23 and L-Selectin (CD62L) From Lymphocytes Is Mediated by the Same Receptor but Different Metalloproteases

Abstract: CD23 is a transmembrane protein expressed on the surface of B-lymphocytes that binds IgE, CD21, CD11b, and CD11c. High concentrations of soluble CD23 and L-selectin are found in the serum of patients with B-chronic lymphocytic leukemia (B-CLL). Because extracellular adenosine triphosphate (ATP) causes shedding of L-selectin via activation of P2Z/P2X7 receptors expressed on B-CLL lymphocytes, we studied the effect of ATP on shedding of CD23. ATP-induced shedding of CD23 at an initial rate of 12% of that for L-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(65 citation statements)
references
References 35 publications
2
61
1
1
Order By: Relevance
“…To our surprise, therefore, in conducting equivalent experiments using lymphocytes from GSK P2X 7 Ϫ/Ϫ mice, we have found that T cells in this strain exhibit high levels of P2X 7 activity. Moreover, unlike previous studies, the activity we report here is unambiguously that of the genuine P2X 7 receptor, reflecting the unique ability of this channel to evoke, when stimulated, the rapid translocation of phosphatidylserine (PS) to the cell surface and cell death [2,15], as well as shedding of the lymphocyte homing receptor CD62 ligand (CD62L) [16].…”
Section: Introductioncontrasting
confidence: 67%
“…To our surprise, therefore, in conducting equivalent experiments using lymphocytes from GSK P2X 7 Ϫ/Ϫ mice, we have found that T cells in this strain exhibit high levels of P2X 7 activity. Moreover, unlike previous studies, the activity we report here is unambiguously that of the genuine P2X 7 receptor, reflecting the unique ability of this channel to evoke, when stimulated, the rapid translocation of phosphatidylserine (PS) to the cell surface and cell death [2,15], as well as shedding of the lymphocyte homing receptor CD62 ligand (CD62L) [16].…”
Section: Introductioncontrasting
confidence: 67%
“…A possible candidate is a 'chemoattractant/chemokine' synthesized or released by endothelial cells. Extracellular ATP can stimulate the shedding of L-selectin as well as CD23 from lymphocytes (Gu et al, 1998) and since ATP can be secreted from endothelial cells (Milner et al, 1990), the role of purinergic mechanisms in transendothelial migration was studied. Thus lymphocytes were pretreated with oxATP to irreversibly inactivate the P2Z/P2X 7 receptor (Murgia et al, 1993;Wiley et al, 1994) prior to the migration assay.…”
Section: Discussionmentioning
confidence: 99%
“…Some CD23 material with apparent high molecular weight was also detected in cell-free supernatants. This diffuse smear could come from multimeric forms of shorter sCD23 fragments often observed after SDS-PAGE separation (46). Cathepsin G treatment also led to the release of essentially short fragments (not shown).…”
Section: Fragments Released By Hlementioning
confidence: 92%